Students’ perceptions of electronic’s module in physics practicum - Darmaji Darmaji; Dwi Agus Kurniawan; Astalini Astalini; Wawan Kurniawan; Khairul Anwar; Artha Lumbantoruan (Intelektual Pustaka Media Utama, 2019)
This study aims to determine the views of students majoring in mathematics education and natural science faculty of teacher training and education science at Universitas Jambi to use electronic’s module in physics practicum which is based on science process skills. The study involved 117 students majoring in mathematics education and science which consists of 59 students of physical education and 58 students of mathematics education. This research is descriptive quantitative research in order to obtain information mean (M), median (Me), mode (Mo), percentage, the range of the maximum value and the minimum value. Data was collected by using questionnaires and interviews. Based on the research results from students’ perceptions of physical education in good category at 64.4% while the student's perception of mathematics education in good category amounting to 55.2%.